"It's all outward appearance-based attractions": A qualitative study of body image among a sample of young gay and bisexual men. Issue 3 (2nd July 2020) - Tran, Alvin; Kaplan, Justin A.; Austin, S. Bryn; Davison, Kirsten; Lopez, Gilberto; Agénor, Madina
Abstract: This study explores the body image ideals among a racially/ethnically diverse sample of gay and bisexual men in the United States. Furthermore, it examines the role body image ideals play on mobile dating applications ("dating apps") for gay and bisexual men. Guided by Objectification Theory and Minority Stress Theory, 30 semi-structured interviews were conducted with young gay and bisexual men (ages 18-30 years) in Massachusetts. Using thematic analysis, three central themes emerged: 1) the ideal male body: muscular, thin, and light-skin toned; 2) discrimination; 3) navigating deviations from the ideal body: appearance comparison, retaliation, and body regulation and weight control behaviors. Our results suggest the dominant ideal male body is muscular and thin. Racial/ethnic minority participants added this ideal is further characterized as white/light-skin toned. Further, participants reported a wide variety of discriminatory experiences on dating apps, especially men deviating from the dominant body ideal. Over half of the men in our sample who reported use of dating apps recounted at least one experience of racial/ethnic discrimination or body weight and shape discrimination on dating apps. While some dating apps have modified their policies to promote inclusivity, further research into the impact of dating app-mediated discrimination are warranted.